Novel functions of CCM1 delimit the relationship of PTB/PH domains - Zhang, Jun (Biochim Biophys Acta Proteins Proteom, 2017)
BACKGROUND: Three NPXY motifs and one FERM domain in CCM1 makes it a versatile scaffold protein for tethering the signaling components together within the CCM signaling complex (CSC). The cellular role of CCM1 protein remains inadequately expounded. Both phosphotyrosine binding (PTB) and pleckstrin homology (PH) domains were recognized as structurally related but functionally distinct domains. METHODS: By utilizing molecular cloning, protein binding assays and RT-qPCR to identify novel cellular partners of CCM1 and its cellular expression patterns; by screening candidate PTB/PH proteins and subsequently structurally simulation in combining with current X-ray crystallography and NMR data to defined the essential structure of PTB/PH domain for NPXY-binding and the relationship among PTB, PH and FERM domain(s). RESULTS: We identified a group of 28 novel cellular partners of CCM1, all of which contain either PTB or PH domain(s), and developed a novel classification system for these PTB/PH proteins based on their relationship with different NPXY motifs of CCM1. Our results demonstrated that CCM1 has a wide spectrum of binding to different PTB/PH proteins and perpetuates their specificity to interact with certain PTB/PH domains through selective combination of three NPXY motifs. We also demonstrated that CCM1 can be assembled into oligomers through intermolecular interaction between its F3 lobe in FERM domain and one of the three NPXY motifs. Despite being embedded in FERM domain as F3 lobe, F3 module acts as a fully functional PH domain to interact with NPXY motif. The most salient feature of the study was that both PTB and PH domains are structurally and functionally comparable, suggesting that PTB domain is likely evolved from PH domain with polymorphic structural additions at its N-terminus. CONCLUSIONS: A new β1A-strand of the PTB domain was discovered and new minimum structural requirement of PTB/PH domain for NPXY motif-binding was determined. Based on our data, a novel theory of structure, function and relationship of PTB, PH and FERM domains has been proposed, which extends the importance of the NPXY-PTB/PH interaction on the CSC signaling and/or other cell receptors with great potential pointing to new therapeutic strategies. GENERAL SIGNIFICANCE: The study provides new insight into the structural characteristics of PTB/PH domains, essential structural elements of PTB/PH domain required for NPXY motif-binding, and function and relationship among PTB, PH and FERM domains.